Cultural Perspectives on Climate Change Adaptation in Agriculture an Ethnoecological Study - Yohanes Kamakaula (Westscience Press, 2024)
In an era where climate change is becoming increasingly apparent, adaptation in the agricultural sector is becoming more crucial. This research adopts a literature study approach to explore the cultural perspective on climate change adaptation in agriculture through the lens of ethnoecology. Through searching and analyzing relevant literature, the main findings indicate that local culture plays a significant role in shaping farmers' adaptation practices. These practices include the utilization of traditional knowledge, cultural values, and local knowledge systems to respond to the challenges of climate change. It is found that local wisdom is not merely an additional resource but an integral aspect in strengthening the resilience of farming communities. However, challenges such as limited access to resources and economic uncertainty remain barriers to adaptation efforts. Therefore, the integration of local knowledge into policy planning and the development of local capacity are relevant recommendations to enhance climate change adaptation in agriculture. This research provides insights into the complexity of the relationship between culture and climate change adaptation in agriculture, highlighting the importance of strengthening the involvement of local communities in mitigation and adaptation efforts.